2011
DOI: 10.1128/aem.03005-10
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Biofilm Matrix-Associated Proteins from an Acid Mine Drainage Microbial Community

Abstract: In microbial communities, extracellular polymeric substances (EPS), also called the extracellular matrix, provide the spatial organization and structural stability during biofilm development. One of the major components of EPS is protein, but it is not clear what specific functions these proteins contribute to the extracellular matrix or to microbial physiology. To investigate this in biofilms from an extremely acidic environment, we used shotgun proteomics analyses to identify proteins associated with EPS in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 64 publications
(69 reference statements)
1
45
0
Order By: Relevance
“…Several studies have been carried out to identify the matrix proteome of several microorganisms, including Vibrio cholerae (19), Pseudomonas aeruginosa (20), Myxococcus xanthus (21) and natural biofilm communities of acid mine drainage (22). These studies revealed that, in addition to secreted proteins, the biofilm matrix also contains large numbers of periplasmic, cytoplasmic, inner, and outer membrane proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been carried out to identify the matrix proteome of several microorganisms, including Vibrio cholerae (19), Pseudomonas aeruginosa (20), Myxococcus xanthus (21) and natural biofilm communities of acid mine drainage (22). These studies revealed that, in addition to secreted proteins, the biofilm matrix also contains large numbers of periplasmic, cytoplasmic, inner, and outer membrane proteins.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to EPS, inorganic materials (minerals) may also be incorporated to provide structural support where physical stresses may impact survival (13). Biofilm formation is known to enhance survival against a range of environmental stresses, such as pH shifts (14), with some biofilm communities creating more favorable growth conditions by secreting specific components of EPS (15,16). In these cases, biofilm formation enables microbial propagation in extreme environments (16,17).…”
mentioning
confidence: 99%
“…Shotgun proteomics has now been applied to biofilm samples for metaproteomics studies of cellular and extracellular proteins (197, 198) and for characterizing the effects of biofilm growth, environmental conditions, and intercellular signaling of individual strains of biofilm organisms (e.g., 199203). Shotgun proteomics uses direct digestion of a complex protein sample with trypsin and LCMS analysis of the ensuing peptide mixture (204).…”
Section: Omics Approaches To Biofilm Studiesmentioning
confidence: 99%